Problematika Pengujian Peraturan Perundang-Undangan Di Mahkamah Agung ( Kajian Terhadap Putusan Mahkamah Agung No. 65 P/HUM/2018) - Suparto Suparto (Faculty of Law, Universitas Pattimura, 2021)
The Supreme Court (MA) decided that candidates for members of the Regional Representative Council (DPD) from political party administrators for the 2019 Election were still allowed, even though previously the Constitutional Court (MK) had banned it (Decision No. This conflict is due to differences in interpreting the timing of the implementation of the ongoing 2019 Election stage process. The Constitutional Court stated that the decision was enforced since the 2019 Election and this was not retroactive. Because it is still at the Provisional Candidate List (DCS) stage, so it is possible to change regulations. Meanwhile, the Supreme Court considers that the Constitutional Court's decision must be enforced after the 2019 Election or apply in the future (prospective), because the stages have been running, so that changes in requirements can be made The legal implication that occurs is that there is legal uncertainty for the General Election Commission (KPU) to follow which decision. To solve this problem can be used the doctrine of validity (enforceability of norms). The existence of a hierarchy of legal products being tested and a basis for testing certainly has a legal consequence of the existence of a hierarchy of norm validity in the decisions of the Supreme Court and the Constitutional Court. When there is a conflict between the Supreme Court decision and the Constitutional Court, the verdict with the basis and object of examination in the hierarchy of laws and regulations that is higher, namely the Constitutional Court decision, has a higher validity than the Supreme Court decision. So that problems like this do not exist anymore, testing of laws and regulations should only be carried out by one institution, namely the Constitutional Court.